Plasmodium matutinum Transmitted by Culex pipiens as a Cause of Avian Malaria in Captive African Penguins (Spheniscus demersus) in Italy - Iurescia, Manuela; Romiti, Federico; Cocumelli, Cristiano; Diaconu, Elena Lavinia; Stravino, Fiorentino; Onorati, Roberta; Alba, Patricia; Friedrich, Klaus Gunther; Maggi, Flavio; Magliano, Adele; Ermenegildi, Arianna; Carfora, Virginia; et al. (Frontiers in Veterinary Science, 2021)
Avian malaria is a parasitic disease of birds caused by protozoa belonging to the genus Plasmodium, within the order Haemosporida. Penguins are considered particularly susceptible, and outbreaks in captive populations can lead to high mortality. We used a multidisciplinary approach to investigate the death due to avian malaria, occurred between 2015 and 2019, in eight African penguins (Spheniscus demersus) kept in two Italian zoos located in central Italy, and situated about 30 km apart. We also provided information about the presence and circulation of Plasmodium spp. in mosquitoes in central Italy by sampling mosquitoes in both zoos where penguin mortalities occurred. In the eight dead penguins, gross and histopathological lesions were consistent with those previously observed by other authors in avian malaria outbreaks. Organs from dead penguins and mosquitoes collected in both zoos were tested for avian malaria parasites by using a PCR assay targeting the partial mitochondrial conserved region of the cytochrome b gene. Identification at species level was performed by sequencing analysis. Plasmodium matutinum was detected in both dead penguins and in mosquitoes (Culex pipiens), while Plasmodium vaughani in Culex pipiens only. Parasites were not found in any of the PCR tested Aedes albopictus samples. Based on our phylogenetic analysis, we detected three previously characterized lineages: Plasmodium matutinum LINN1 and AFTRU5, P. vaughani SYAT05. In Culex pipiens we also identified two novel lineages, CXPIP32 (inferred morphospecies Plasmodium matutinum) and CXPIP33 (inferred morphospecies P. vaughani). Significantly, LINN1 and AFTRU5 were found to be associated to penguin deaths, although only LINN1 was detected both in penguins (along the years of the study) and in Culex pipiens, while AFTRU5 was detected in a single penguin dead in 2017. In conclusion, in our study Plasmodium matutinum was found to cause avian malaria in captive penguins kept in Europe, with Culex pipiens being its most probable vector. Our results are in agreement with previous studies suggesting that Culex pipiens is one of the main vectors of Plasmodium spp. in Europe and the Northern Hemisphere. Zoos maintaining captive penguins in temperate areas where Culex pipiens is abundant should be well aware of the risks of avian malaria, and should put every effort to prevent outbreaks, in particular during the periods when the number of vectors is higher.